Reaction balancer functionality in Metapenta (2024)
This project introduces a new functionality focused on reaction balance within the pre-existing MetaPenta software, with the purpose of automating a crucial step in the reconstruction of genome-scale networks. The novel module allows the generation of a complete report pointing out unbalanced reactions from the target metabolic network. This report also details the successfully balanced reactions, specifying modifications made on both sides of each reaction and the method that was used. The motivation for this development emerges from the observed limitations in current tools available designed for genome-scale metabolic reconstruction, which still lack the capability to autonomously curate the first draft. Consequently, researchers currently have to verify manually which reactions are not balanced by calculating the stoichiometry of each reaction. Therefore, the introduced reaction balancer functionality automates the evaluation of each reaction in the metabolic network aiming to balance as many reactions as feasible. In this way, the automation improves the curation process by augmenting the performance and reliability of genome-scale metabolic reconstructions.